DETECTION OF SAG1 AND BAG1 Toxoplasma gondii DNA PROBES LABELLED WITH DIGOXIGENIN-11-dUTP - Ida Ayu Pasti Apsari; Wayan Tunas Artama; Sumartono s; I Made Damriyasa (Universitas Syiah Kuala, 2013)
The objective of this research was to detect a minimum concentration of the probes that could be used for dot blot hybridization analysis. The method required labeled DNA probes. In this study a non-radioactive label of Digoxigenin-11-dUTP was used for labeling the Sag1 and the Bag1 of Toxoplasma gondii DNA probe. Labeling method for the probes was done according to the random primed labeling technique. The result showed that 0.67 pg/µl Sag1 probe and 0.58 pg/µl Bag1 probe could be detected by anti-Dig-antibody. It could be concluded that 0.67 pg/µl Sag1 probe and 0.58 pg/µl Bag1 probe could be used to diagnose toxoplasmosis by dot blot hybridization method.